Monthly averages of nitrous oxide and ozone for the Northern and Southern Hemisphere high latitudes: A "one-year climatology" derived from ILAS/ILAS-II observations - Khosrawi, F.; Müller, R.; Proffitt, M. H.; Nakajima, H. (Journal of Geophysical Research, 2006)
[1] Correlations of ozone (O-3) and nitrous oxide (N2O) have been suggested as a tool for validating photochemical models and as a reference for estimating high-latitude ozone loss. However, so far no analysis of ozone-tracer relations is available that provides a good temporal coverage during all months. Here we combine measurements from the Improved Limb Atmospheric Spectrometers (ILAS/ILAS-II) to derive an O-3/N2O climatology for the high-latitude regions in the Northern and Southern Hemisphere for each month of the year, thus providing a complete seasonal cycle. ILAS and ILAS-II operated on board the Advanced Earth Observing Satellite (ADEOS/ADEOS-II), and both instruments use the solar occultation technique. ILAS operated for 8 months in 1996/ 1997, and ILAS-II operated for 7 months in 2003. The ILAS-II measurements cover the months that are not available from ILAS. The ILAS/ILAS-II correlations of ozone versus nitrous oxide are organized monthly in both hemispheres by partitioning these data into equal bins of altitude or potential temperature. The resulting families of curves allow separation of ozone changes due to photochemistry from those due to transport. The combined ILAS/ILAS-II data set corroborates earlier findings that the families of O-3/N2O curves are separated and generally do not cross and further that the separation is much clearer for the potential temperature binning than for the altitude binning. The much clearer separation for the potential temperature binning is due to transport being predominantly isentropic. Thus these curves are particularly suitable for the validation of photochemical models. The seasonal cycle of O-3/N2O distributions in the Northern and Southern Hemisphere high latitudes is found to be rather different. In the Southern Hemisphere, O-3/N2O distributions are influenced by the strong chemical ozone loss in the Antarctic vortex and by a much longer duration of the polar vortex. In the Northern Hemisphere, diabatic descent is much more pronounced. Solely during the ...